Reorganizing health care delivery systems problems of managed care and other models of health care delivery - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2003)
This volume deals with the reorganizing of health care delivery systems: problems of managed care and other models of health care delivery. Issues of how to best organize a health care delivery system are not new, but the amount of interest in this topic in the US (as well as in other countries) has grown in recent decades. Reorganizing health care delivery systems is a concern of many systems of the world, and this volume contains some papers from countries other than the US, although the majority of the papers do relate issues to the US health care delivery system. While most papers relate to structural and organizational factors, the impact of individual patients is not neglected. The volume contains 11 papers, organized into four sections. The sections cover managed care issues and organizational features, special groups of patients and health issues, lessons from other countries, and broader policy concerns and health insurance reform. This book addresses important themes in medical sociology, with papers that range from those with an explicit policy point of view to narrower papers on more specific issues in health care delivery. It aims to contribute to improving our understanding of these issues and provides a sociological focus for the exploration of them. This should make the volume essential reading for medical sociologists and other social scientists studying health care delivery issues. The information should be also helpful to health services researchers, policy analysts and public health researchers.